TYPOLOGY OF PORTUGUESE FORTRESS AS PART OF SITUATIONAL DEFENSE SYSTEM - Widyaning , Andhini Widyaning; H, Arum Alifia; P, Fadilla Ayu; N, Risma Zuhriyatun (ADBE, 2025)
Jepara is the capital of Jepara regency as well as the center of government and economy of Jepara Regency. The Portuguese Fort is one of the places that is a reminder of the Portuguese colonization in Indonesia in the past. This fort serves to supervise Dutch ships passing in the sea around the fort, as soon as a Dutch ship passes, it will be fired upon by Portuguese troops. But after being abandoned by the Portuguese, this fortress was used by the Japanese as a sea reconnaissance site. The purpose of this study is to examine the relationship of situational defense architecture to the spatial typology found in the Portuguese Fort. This study uses a qualitative analysis method with data collection on pre-existing literature studies related to the existence of the Portuguese Fort. The results of this study show that the typology of the Portuguese Fort has been in accordance with the situational defense system from the physical shape of the fortress that is typical of the coastal area so that it needs to be used as a cultural heritage site because its existence is important for the history of Jepara.